Nuclear-mitochondrial communication involving miR-181c plays an important role in cardiac dysfunction during obesity. (July 2020) - Roman, Barbara; Kaur, Pawandeep; Ashok, Deepthi; Kohr, Mark; Biswas, Roopa; O'Rourke, Brian; Steenbergen, Charles; Das, Samarjit
Abstract: Aims: In cardiomyocytes, there is microRNA (miR) in the mitochondria that originates from the nuclear genome and matures in the cytoplasm before translocating into the mitochondria. Overexpression of one such miR, miR-181c, can lead to heart failure by stimulating reactive oxygen species (ROS) production and increasing mitochondrial calcium level ([Ca 2+ ]m ). Mitochondrial calcium uptake 1 protein (MICU1), a regulatory protein in the mitochondrial calcium uniporter complex, plays an important role in regulating [Ca 2+ ]m . Obesity results in miR-181c overexpression and a decrease in MICU1. We hypothesize that lowering miR-181c would protect against obesity-induced cardiac dysfunction. Methods and results: We used an in vivo mouse model of high-fat diet (HFD) for 18 weeks and induced high lipid load in H9c2 cells with oleate-conjugated bovine serum albumin in vitro. We tested the cardioprotective role of lowering miR-181c by using miR-181c/d −/− mice ( in vivo ) and AntagomiR against miR-181c ( in vitro ). HFD significantly upregulated heart levels of miR-181c and led to cardiac hypertrophy in wild-type mice, but not in miR-181c/d −/− mice. HFD also increased ROS production and pyruvate dehydrogenase activity (a surrogate for [Ca 2+ ]m ), but the increases were alleviated in miR-181c/d −/− mice. Moreover, miR-181c/d −/− mice fed a HFD had higher levels of MICU1 than did wild-type mice fed a HFD, attenuating the rise in [Ca 2+ ]m . Overexpression of miR-181c in neonatal ventricular cardiomyocytes (NMVM) caused increased ROS production, which oxidized transcription factor Sp1 and led to a loss of Sp1, thereby slowing MICU1 transcription. Hence, miR-181c increases [Ca 2+ ]m through Sp1 oxidation and downregulation of MICU1, suggesting that the cardioprotective effect of miR-181c/d −/− results from inhibition of Sp1 oxidation. Conclusion: This study has identified a unique nuclear-mitochondrial communication mechanism in the heart orchestrated by miR-181c. Obesity-induced overexpression of miR-181c increases [Ca 2+ ]m via downregulation of MICU1 and leads to cardiac injury. A strategy to inhibit miR-181c in cardiomyocytes can preserve cardiac function during obesity by improving mitochondrial function. Altering miR-181c expression may provide a pharmacologic approach to improve cardiomyopathy in individuals with obesity/type 2 diabetes. Graphical abstract: Unlabelled Image Highlights: Diet-induced obesity upregulates miR-181c expression in the heart. A high fat diet leads to upregulated miR-181c, which translocates into the mitochondria. miR-181c activates Sp1 degradation by post-translational modification at cystine residue(s). Upregulation of miR-181c causes transcriptional inhibition of the MICU1 gene.